2021
DOI: 10.3389/fcvm.2021.705273
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Serum Fibroblast Growth Factor 21 Concentration Is Closely Associated With an Increased Risk of Cardiovascular Diseases: A Systematic Review and Meta-Analysis

Abstract: Background: The association between fibroblast growth factor 21 (FGF21) and cardiovascular disease (CVD) risk remains unclear. We conducted this systematic review and meta-analysis to evaluate the association between FGF21 and CVDs, and relevant vascular parameters.Methods: PubMed and Web of Science databases were systematically searched to identify relevant studies published before March 2021. The FGF21 concentration was compared between individuals with and without CVDs. The effect of FGF21 on CVD risk was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Several studies have revealed the intrinsic link between FGF21 and CAD. Zhang Y et al analyzed a large population and discovered that high levels of circulating FGF21 were strongly associated with increased risk of CAD (23). A cross-sectional study in a Chinese population unmasked that serum FGF21 levels in CAD patients increased with the severity of metabolic disorders, independent of age, gender and BMI (24).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the intrinsic link between FGF21 and CAD. Zhang Y et al analyzed a large population and discovered that high levels of circulating FGF21 were strongly associated with increased risk of CAD (23). A cross-sectional study in a Chinese population unmasked that serum FGF21 levels in CAD patients increased with the severity of metabolic disorders, independent of age, gender and BMI (24).…”
Section: Discussionmentioning
confidence: 99%
“…Lakhani et al analysed FGF21 in different cardiometabolic disorders, including metabolic syndrome, diabetes, diabetic nephropathy, CAD, and cardiovascular motality, and reported elevated FGF21 levels were significant predictors of these disorders [105]. Although these findings were subsequently confirmed by Zhang et al [26], both of these reports identified moderate-to-significant heterogeneity between studies which may impact the validity of the results.…”
Section: Circulating Fgf21 Levels and Atherosclerotic Cvds In Humansmentioning
confidence: 98%
“…In humans, circulating FGF21 levels are elevated in metabolic syndrome, obesity, CVDs, diabetes, non-alcoholic fatty liver disease, mitochondrial myopathies, and cold exposure [26,38,[62][63][64][65][66][67][68][69]. Given the beneficial metabolic effects of FGF21 that have been demonstrated in vitro, the paradoxical increase reported in these conditions is thought to be due to an FGF21 resistant state, caused by the impaired FGF21 signalling which results in the need for a higher FGF21 level to exert its beneficial metabolic effects [43,70,71].…”
Section: Metabolic Functions Of Fgf21mentioning
confidence: 99%
See 1 more Smart Citation
“…cFGF21 levels have been shown to be elevated in subjects with metabolic syndrome, nonalcoholic fatty liver, hyperlipidemia, and cardiovascular diseases ( 9 , 10 ). Thus, cFGF21 is regarded as a useful biomarker of metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%